Psychology, Psychotherapy and Society: Humanistic and Existential Remarks - Arbocco De los Heros, Manuel (2015)
Some ideas about man and society are shared in this article. A brief listing of problems such as “light” relationships, consumerism, technology, and isolation and the desire of having rather than being is shown here. Topics like welfare, meaning of life, the importance of the sense of humor and the thought of a vital project are also considered. Every aspect is analyzed within a look of Humanistic Psychology and Existential Psychotherapy. We hope these notes will generate more remarks and new proposals and stir consciences.